Dampak Kekerasan Orang Tua bagi Anak - Siti Amanah; Chalista Hafizah; Sasa Bilkis (Departement of Mathematics Education, 2023)
The study is set back by a child who experiences the effects of parental abuse on a child. The purpose of this study is to describe the parent’s abuse of children seen from: 1) physical impact;2) psychological impact. It is a qualitative study of case study. The RH key informant and 2 additional informers made up of 1 RH client friend and 1 RH domestic assistant who was experiencing parental abuse. The study was focused on the effects of parental abuse on children in both physical and psychological aspects. The instruments used in this study are guidelines of observation and interview guidelines, techniques used in data processing through data reduction, data presentation and deduction. Research revealed that the physical effects of the RH client were of bruising and scrapes, of sleeping disorders after beatings, of silence when asked what was befallen him; 2) the psychological impact of the RH is that of feeling sadness, fear and shame, worry, worry, low self-esteem, low self-esteem, and often isolation and isolation from friends. According to the issues at hand, RH was given a consultation to treat his parents’ abuse without interfering with his psychological development.